Favourable adsorption and sensing properties of Pd-doped SnSSe monolayer towards H2 and C2H2 in the oil-immersed transformers. (3rd July 2022) - Zhang, Keyong; Yao, Wei; Jin, Yaoke; Jia, Zihao; Wu, Xibo; Dong, Dalei
Abstract : This work based on the first-principles theory simulates the Pd-doping behaviour on the SnSSe monolayer and the sensing properties of Pd-doped SnSSe (Pd-SnSSe) monolayer towards two dissolved gas species, namely H2 and C2 H2, aiming at exploring its potential as a chemical gas sensor to evaluate the operation status of the on-load tap-changer in the oil-immersed transformers. The Pd atom preferred to be doped on the Se-surface of the SnSSe monolayer with the formation energy ( E form ) of 0.18 eV. The Pd-SnSSe monolayer behaves physisorption upon H2 while chemisorption upon C2 H2 with E ad calculated as −0.20 and −0.87 eV, respectively. The BS results and the recovery property analysis reveal the strong potential of Pd-SnSSe monolayer as a C2 H2 sensor with high sensitivity of −85.5% and good reusability with a recovery time of 510.1 s at room temperature. On the other hand, it is not suitable to explore the Pd-SnSSe monolayer as a reusable resistance-type sensor for H2 detection, nor as an optical sensor for H2 and C2 H2 detections. This work gives a new insight into the Janus SnSSe monolayer for gas sensing application, which is beneficial for further exploration of SnSSe-based materials to be applied in the field of electrical engineering. GRAPHICAL ABSTRACT: UF0001